Investigating The Mechanism Of Confronting Earthquake Crisis, With The Approach Of Rehabilitation Of Urban Worn Textures - Shivaei, Asma; Rahimi, Mohammad (The Turkish Online Journal of Design Art and Communication, 2016)
Seismic rehabilitation of structures subjected to earthquake is one of the most important engineering issues in earthquake-prone countries all over the world. Vast areas in the existing structures which are located in earthquake-prone areas do not enjoy enough seismic safety. The structure can be restored by using different rehabilitation techniques in order to avoid possible problems during severe earthquakes. There are several methods for seismic rehabilitation of structures and the designing engineer must select the most economical approach with the best performance during the earthquake. In this paper, at first the earthquake crisis has been defined and management methods have been expressed, through using library resources and qualitative-analytical methods. Then we have studied different buildings and their rehabilitation and renovation methods and finally we achieved a set of rehabilitation and crisis management strategies.
Keywords: earthquake; rehabilitation; worn textures